The Role of Parents' and Teachers' Responsibilities for Children's Education from an Islamic Perspective - Ubaidillah, Ubaidillah; Purnawati, Putri; Najibah, Ainun; Hana, Hana (PT. BATARI EDU CALYA, 2024)
Education is a human right, especially for children. If ignored, there will be chaos in all aspects of life because of ignorance. In this article, we discuss the educational responsibilities of children, these responsibilities are